Examination of the lipid profile, antioxidant capacity, and impact of Sida linifolia L. extract on the liver and kidney functions of mice infected with malaria (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
The study aimed to investigate the impact of treatment with the ethanolic leaf extract of Sida linifolia (ELES) in malaria-infected mice and the effect of the extract on tissues and organs. Phytochemical screening was conducted, and the liver and kidney function parameters, lipid profile, antioxidant parameters, and electrolyte status were determined. From the findings of the study, tannins, saponins, flavonoids, steroids, and other phytochemicals were detected. The activities of alkaline phosphatase, aspartate aminotransferase, superoxide dismutase, and total protein, triacylglycerol, high-density lipoproteins, and electrolytes concentrations of the infected animals treated with different doses of the extract were significantly (p